Legal Approach in Proving and Providing Sanctions for Sexual Gratification Cases in Indonesia - Stephanie Christy; Benny Djaja (Greenation International Journal of Law and Social Sciences, 2024)
Corruption is a serious crime that broadly threatens social, economic, and political balance and weakens the legal foundation and ethical values in society. In Indonesia, corrupt practices are increasingly diverse, one of which is gratuities in the form of sexual services, which existing regulations have not fully covered. Although Indonesia's Corruption Eradication Law has regulated various types of gratuities, there are no explicit rules regarding sexual services, creating potential legal uncertainty. In contrast, Singapore through the Prevention of Corruption Act (PCA) has established clear rules related to sexual gratification as a form of offense that can be subject to legal sanctions. Based on this comparison, Indonesia needs more comprehensive regulations related to sexual gratification to deal with increasingly complex modes of corruption so that effectiveness in preventing and eradicating corruption in various sectors can be further enhanced.